Understanding the discourse of gender dysphoria in the realm of Islamic scholarly discussion - Mahmad Robbi, Ahmad Akram (CENTRE FOR ISLAMISATION, 2024)
This study explores the discourse surrounding gender dysphoria within Islamic scholarly discussions, aiming to understand how contemporary Islamic thought navigates the complexities of gender identity issues. Utilising qualitative research field, this study is examining classical and modern Islamic jurisprudence, as well as theological perspectives, delving into the ways Islamic scholars address the nuances of gender dysphoria, considering the implications of both traditional interpretations and evolving contemporary views. Ultimately, this research seeks to contribute to a deeper understanding of how Islamic scholarship engages with the challenges posed by gender dysphoria in the modern context.